Mechanisms of Disease: hepatic steatosis in type 2 diabetes—pathogenesis and clinical relevance - Roden, Michael (Nature clinical practice. Endocrinology & metabolism, 2006)
Excess free fatty acids, an imbalance of adipocytokines and mitochondrial dysfunction all contribute to abnormalities in hepatocellular lipid content in diabetes and can lead to steatosis and insulin resistance. Thus liver fat is a novel target for therapies such as fat-reduced diets and thiazolidendiones. Hepatic steatosis is defined by an increased content of hepatocellular lipids (HCLs) and is frequently observed in insulin-resistant states including type 2 diabetes mellitus. A dietary excess of saturated fat contributes significantly to HCL accumulation. Elevated HCL levels mainly account for hepatic insulin resistance, which is probably mediated by partitioning of free fatty acids to the liver (fat overflow) and by an imbalance of adipocytokines (decreased adiponectin and/or increased proinflammatory cytokines). Both free fatty acids and adipocytokines activate inflammatory pathways that include protein kinase C, the transcription factor nuclear factor κB, and c-Jun N-terminal kinase 1 and can thereby accelerate the progression of hepatic steatosis to nonalcoholic steatohepatitis and cirrhosis. Proton magnetic resonance spectroscopy has made it possible to quantify HCL concentrations and to detect even small changes in these concentrations in clinical settings. Moderately hypocaloric, fat-reduced diets can decrease HCL levels by ∼40–80% in parallel with loss of up to 8% of body weight. Treatment with thiazolidinediones (e.g. pioglitazone and rosiglitazone) reduces HCL levels by 30–50% by modulating insulin sensitivity and endocrine function of adipose tissue in type 2 diabetes. Metformin improves hepatic insulin action without affecting HCL levels, whereas insulin infusion for 67 h increases HCL levels by ∼18%; furthermore, HCL levels positively correlate with the insulin dosage in insulin-treated type 2 diabetes. In conclusion, liver fat is a critical determinant of metabolic fluxes and inflammatory processes, thereby representing an important therapeutic target in insulin resistance and type 2 diabetes mellitus. Key Points Hepatic steatosis is diagnosed when more than 5% of the content of liver cells is lipid and is typical in insulin-resistant states, including type 2 diabetes mellitus Free fatty acids (fat overflow) and imbalance of adipocytokines contribute to elevated hepatocellular lipid (HCL) levels and hepatic insulin resistance Mitochondrial dysfunction and activation of inflammatory pathways seem to be the major intracellular mechanisms determining hepatic steatosis and its progression to nonalcoholic steatohepatitis Proton magnetic resonance spectroscopy allows quantification of HCL concentrations in clinical settings Fat-reduced diets and thiazolidinediones decrease HCL levels by ∼30–80%, whereas insulin infusion increases HCL levels by ∼18% Liver fat is a novel therapeutic target in insulin resistance and type 2 diabetes mellitus